Adsorbs! Fenol Dengan Adsorben Kitin - Yenti, Silvia Reni (Jurnal Pilar Sains, 2011)
Phenol into the waters have an impact on environmental pollution when the phenol content of that exceeds the predetermined threshold is 0.001mg/L.Chitin derived from shrimp shell wastes can be utilized as adsorben adsorption of phenol with adsorbtioni.this search process aims to determine the absorption maximum chitin by variations in temperature and concentration of phenol .the treatment shrimp shell waste to obtain chitin includes washing ,dryng,grinding,soaking with HCL 2N to remove minerals (demineralization) and soaking with NaOH 2N TO remove proteins (deproteinasi).then performed the absorption process with adsorption time 60 minutes,stiring speed 150 rpm,temperature variation 30;40;50⁰C and concentration of phenol 50,75,100,125ppm.from searched result is obtained of the absorbed phenol on chitin 5gr amounted to 4,479with concentration of phenol 100ppm at 30⁰C.